The Grain Chain : Food Security and Managing Wheat Imports in Arab Countries - World Bank; FAO (World Bank, Washington, DC, 2016)
Arab countries face a number of food security risks due to their high dependence on wheat imports. This study explores ways in which countries can mitigate these risks. The authors evaluate the wheat import supply chain (WISC) from the unloading port to bulk storage at the flour mill, before the wheat is milled into flour. Existing literature treats isolated topics related to the supply chain, such as strategic storage and the use of financial instruments. This study is unique in that it takes a holistic view of the supply chain by examining how strategic storage, logistics improvements, and procurement strategies can all be used to improve food security. This study considers three critical aspects to the WISC and proposes several strategies Arab countries may consider to mitigate import risks: strategic storage (chapter two): maintain strategic wheat reserves to weather times of crisis and food supply disruptions and to contribute to domestic and international price stabilization effects. Logistics (chapter three): promote investments throughout the supply chain that create smooth logistics, improve security, provide a reliable supply of wheat, reduce the base cost of importing wheat, and reduce product losses. Procurement (chapter four): develop a procurement strategy that leverages strategic partnerships while maintaining a diversified portfolio of suppliers and mitigates import risks through the use of hedging strategies. Currently, overall storage capacity in the region averages the equivalent of six months of consumption, and estimated ending stocks average four and one-half months. However, many Arab countries are planning to increase their strategic wheat reserves as a policy to improve food security. This can provide them with critical lead time to secure alternative wheat supplies or supply routes during times of crisis. Reserves also offer psychological benefits that may prevent hoarding and pilferage.